Prevalence and Clinical Correlates of Dysmagnesemia among Medically Hospitalized Patients at Shar Hospital, Sulaimani, Iraq: A Cross- Sectional Study - Hussein Amin Mahmood, Kawa (Hammurabi Journal of Medical Sciences, 2026)
Background: In more than 300 enzymatic reactions, magnesium (Mg) is the fourth most prevalent cation cofactor. Objectives: to explore dysmagnesemia prevalence and its related clinical characteristics among hospitalised patients at Shar Hospital, Sulaimani, Iraq. Materials and Methods: A cross-sectional study was employed on 252 patients, adults thier ages (≥18 years), over six months duration. In the current study, information on patients' comorbidities, characteristics, medications, and seruim magnisium were obtained. Analytical statistics were performed to find the association, including chi-square . The p-value < 0.05 was considered significant. Results: The prevalence of dysmagnesemia among the cohort group was 50.0%; 18.3% had hypermagnesemia (>2.2 mg/dL), and 31.7% had hypomagnesemia (<1.7 mg/dL). Renal diseases were found to be a significant pathology causing the disturbance in magnesium level, as it founf that sginificant (P 0.021), with 41.3% of hypermagnesemic patients having renal pathology. Hypertension was found to be a borderline significant association (P ≤ 0.056). Other morbidities, suchas cardiac, pulmonary diseases, diabetes, metabolic acidosis, or ECG abnormalities, were found to be not significant. Exposure to proton pump inhibitors and loop diuertics were found to be common among these patients (18.3%) and (24.2%), respectively. Conclusion: Renal diseases were considered the main morbidity associated with dysmagnesemia. The current study underscores the important monitor for the magnesium level among high risk groups.